'Life After Prostate Cancer Diagnosis' study. Issue 4 (July 2015) - Prostate Cancer UK; Movember Foundation
<x xml:space="preserve">Abstract</x> Prostate Cancer UK and the Movember Foundation have funded an expert team of researchers at the University of Leeds, Queens University Belfast, Oxford Brookes University and the University of Southampton to conduct a research study entitled 'Life After Prostate Cancer Diagnosis', which will survey many prostate cancer patients diagnosed with prostate cancer between 1 and 3 years ago using a new patient‐reported outcome measure tool.